1979
DOI: 10.2134/agronj1979.00021962007100040004x
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Index of Soybeans as Affected by Planting Date and Maturity Rating1

Abstract: Selection for high harvest index has been used by plant breeders to improve the seed yield of several crop plants, but in soybean [Glycine max (L.) Merrill] errors in the estimate of harvest index may occur because of interactions with maturity or seeding date and because harvest index measured at maturity does not include leaf and petiole dry weights. The objective of this study was to examine harvest indices of 10 soybean genotypes representing a wide range of maturity and seeded on several dates and to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 8 publications
6
24
1
Order By: Relevance
“…We estimated an HI of 0.36, based on measurements from farms included in this study of plant biomass for Vinton 81 soybeans at peak growth and seed yields at full maturity during previous experiments (unpublished data). This value is in agreement with the average HI value measured by Johnson and Major (1979) across Maturity Group I soybean varieties. We assumed an average seed N concentration of 6.8% N, based on average values measured for Vinton 81 soybean seed N concentration across 15 fields in the study area in 2002, 2003, and 2004 (unpublished data).…”
Section: Implications For Agroecosystem Nitrogen Managementsupporting
confidence: 89%
“…We estimated an HI of 0.36, based on measurements from farms included in this study of plant biomass for Vinton 81 soybeans at peak growth and seed yields at full maturity during previous experiments (unpublished data). This value is in agreement with the average HI value measured by Johnson and Major (1979) across Maturity Group I soybean varieties. We assumed an average seed N concentration of 6.8% N, based on average values measured for Vinton 81 soybean seed N concentration across 15 fields in the study area in 2002, 2003, and 2004 (unpublished data).…”
Section: Implications For Agroecosystem Nitrogen Managementsupporting
confidence: 89%
“…However, soybean plantings following wheat are often delayed due to slow wheat maturation or excess precipitation. Soybean yields are known to decline as much as 43 kg ha −1 d −1 for each day that plantings are delayed beyond the third week of June (Johnson and Major, 1979). Thus, producers often abort plans to plant soybean when faced with July planting dates.…”
Section: Introductionmentioning
confidence: 99%
“…This result contradicts the view that harvest index is a constant across environmental factors (Johnson and Major, 1979), or that harvest index and yield are not related across years (Schapaugh and Wilcox, 1980). However, previous studies have indicated that cultural factors such as planting date and plant population do affect harvest index (Board et al, 1990;Carpenter and Board, 1997).…”
Section: Resultsmentioning
confidence: 71%